Multidisciplinary approach to X-linked hypophosphatemia: A literature review - Falcon-Guerrero, Britto Ebert (2024)
X-linked hypophosphatemia (XLH) is the most common hereditary form of rickets and osteomalacia. It results from dysregulated fbroblast growth factor 23 (FGF23) due to a mutation in the PHEX gene, leading to decreased tubular phosphate reabsorption, reduced renal 1a-hydroxylase activity, and increased renal 24-hydroxylase activity. Patients with XLH present with rickets and osteomalacia, severe lower limb deformities, bone and muscle pain, growth retardation, and reduced quality of life. As a multisystemic disorder, XLH requires a multidisciplinary approach involving highly specialized felds. Severe complications associated with XLH include craniosynostosis, hearing loss, progressive bone deformities, recurrent dental and periodontal lesions, and psychosocial distress. Given these concerns, we conducted a literature review of PLOS ONE and the PubMed and Google Scholar databases, focusing on publications from the past fve years, to refne diagnostic and treatment approaches.